Racial Stigma and Sense of agency: Implications for neurocognitive and social-cognitive research - Anwarzi, Deewa (My University, 2023)
As social creatures, our social encounters matter. They matter for how we experience the world, as well as ourselves. The role of psycho-social experiences has recently been recognized in the neurocognitive literature on the sense of agency. Defined as the experience of control over one’s actions and outcomes, researchers have begun exploring how social interactions and contextual cues modulate this experience, using an implicit task known as intentional binding. This task claims to capture the sense of agency by assessing differences in perception of time across conditions that are theoretically considered to be higher in sense of agency as compared to those that are lower. Drawing inspiration from this new literature, this thesis explores, across five studies, the impact of different psycho-social experiences, particularly those related to stigmatized racial minority groups, on the sense of agency. Our first two studies (n= 36, n=123) indicate that reflection on both negative and positive psycho-social experiences, including racial stigma, bias, and acceptance, reduces the sense of agency, as indexed by lower action-effect interval estimates. Further, our latter three studies (n=45, n=44, n=44), which focus on North American and international samples, suggest that expectations of racial bias reduce the sense of agency and that this reduction is greatest amongst people who experience a threat to their identity because of the event, as well as people who are low-self monitors. Insights from these studies are used to advance neurocognitive and social cognitive work, including psycho-social modulates of intentional binding and psychological mechanisms that affect racial minorities.
Keywords: Sense of agency; Intentional binding; Self-consciousness; Pre-reflective self; Social identity threat; Racial stigma; Race-based experience